PENGARUH SOURCE CREDIBILITY DAN PARASOCIAL RELATIONSHIP TERHADAP PURCHASE INTENTION DAN MODERASI SELF CONGRUITY MENGGUNAKAN STRAY KIDS SEBAGAI ENDORSER - Nuari, Syndi Putri Fitrianti; Setyawan , Andhy (FEB Universitas Sam Ratulangi Manado, 2024)
This study aims to examine the impact of parasocial relationship mediation on the relationship between source credibility (attractiveness, expertise, and trustworthiness) and purchase intention and the moderating effect of self congruity on the relationship between parasocial relationship and purchase intention using Stray Kids as an endorser. This study is a causal research study with a quantitative approach. The sampling collection technique used in the study is non-probability sampling with a purposive sampling type. The target population used in this study are k-pop fans who idolize the boy group Stray Kids and know the Ultra Milk x Stray Kids product. The sample used in the study was 150 respondents. The software used to test the study was smartPLS 3 using the SEM PLS analysis technique. The results of this study indicate that attractiveness has a significant positive impact directly on purchase intention, parasocial relationships mediate the relationship between source credibility and purchase intention, and self congruity is proven to have no moderating effect on the relationship between parasocial relationships and purchase intention.